Factors affecting breasrt milk in post partum mothers at atikah sipolu clinic, panyabungan district, Mandailing Natal - Helmi wardah Nasution; Ferika Desi (Science Midwifery, 2023)
Every year the number of babies and toddlers due to malnutrition continues to increase. Breast milk are milk deposition due to narrowing of the lactefferi or gland ducts, milk is not completely emptied or due to abnormalities in the nipples. The research design is descriptive with a sample of 50 people with the total sampling method. This research was conducted from April 2 to May 8, 2022. The instrument in this study was a questionnaire which included demographic data and a question. The results showed that most of the ASI dam mothers had sufficient knowledge of 40 people (80%) and those with less knowledge were 4 people (8%) and those who had good knowledge were 6 people (12%). ) in overcoming ASI dams in post partum mothers. From the results of this study regarding "Factors Influencing the Incidence of ASI Dams in Post Partum Mothers at the Atikah Sipolu clinic - Polu Panyabungan District, Mandailing Natal" the majority had knowledge of 40 respondents (80%). From this research it is hoped that health workers will further increase counseling and counseling about the importance of breastfeeding and the benefits of breastfeeding problems that occur in mothers who have babies while breastfeeding.